Respuesta :

Y=4x+6 is x=-3/2 Y=2x is x=0

Answer:

(-3, -6)

Step-by-step explanation:

Eliminate the equal sides of each equation and combine.

4x + 6 = 2x

Move all terms containing x to the left side of the equation.

2x + 6 = 0

y = 2x

Subtract 6 from both sides of the equation.

2x = -6

y = 2x

Divide each term by 2 and simplify.

x = -3

y = 2x

Replace all occurrences of x in y = 2x with −3.

x = -3

y = 2 (-3)

Multiply 2 by −3.

x = -3

y = -6

The solution to the system of equations can be represented as a point.

(−3, −6)